Pengaruh Pemberian Berbagai Macam Bahan Organik terhadap Ketersediaan Hara Nitrogen, Fosfor dan Kalium serta Serapan Nitrogen oleh Jagung (Zea mays L.) pada Tanah Ultisols - Ahmad Mustaqim; Hairil Ifansyah; Akhmad Rizalli Saidy (Acta Solum, 2023)
Ultisols distributes spreadly in Indonesia, but this soil has low fertility. Therefore, the application of organic matter (OM) is a common management to increase this soil fertility. The purpose of this study was to determine the role of different types of OM (originated from animals and plants) on the availability of nitrogen, phosphorus, and potassium as well as nitrogen uptake in maize in Ultisols. Soil with a mass of 5 kg without organic matter (control), with the application of chicken manure, cow manure, swallow manure, kirinyuh, babadotan, and kalopo manure were incubated in experimental pots for two weeks at 60% field capacity. After the completion of the incubation period, soil sub-sampling was carried out for the determination of available N, available P and exchangeable K. Furthermore, in each experimental pot, corn seeds were planted, and the observations of dried-weight of corn and nitrogen uptake in corn were observed in a vegetative phase. The results showed that the application of different types of organic matter increased soil pH, nitrate content, exchangeable K, plant dried-weight and plant nitrogen uptake. The content of ammonium and available P was not affected by OM addition. The results also showed that OM derived from animals resulted in higher increases in pH and exchangeable K than those derived from plants. However, OM derived from plants resulted in higher increases in nitrate, plant dry weight and better plant N uptake than OM from animal waste. The results of this study show that the application of OM results in increases in some soil chemical properties, in which the degree of increases in soil chemical characteristics is controlled by the OM origin.